THE EFFECT OF BRAND EQUITY ON PRICE PREMIUM OF APPLE IPHONE - Jacques, Matthew Whampy Limpele (Universitas Sam Ratulangi, 2013)
Consumers often judge the quality of a certain product with the basis of information. Some information providing a specific product characteristic while others are extrinsic to the product such as the buyer’s perception of price, store and brand name. There are some examples of specific product characteristics, such as the volume, ingredients, and product origin. There are two main objectives in this research, including: To understand the effect of brand equity on price premium of Apple iPhone and to identify which variable of brand equity that has the most significant effect on price premium of Apple iPhone. Theories supporting this research are brand equity and price premium. The population is consumers of Apple iPhone with sample of 100 customers using Multiple Regression Analysis Model. Results and conclusions show that (1) all independent variables have strong and positive relationship with price premium, (2) perceived quality, brand awareness, brand association, and uniqueness influence price premium but brand loyalty has no significant influence on price premium (3) uniqueness is the most influence factors to price premium which can explain the differences of Apple iPhone. Based on this research, customers in Manado should rethink and consider more to purchase an Apple iPhone and Apple as company should increase the relationship with customers in Manado to enhance the brand loyalty. Keywords: brand equity, price premium